Eastern aspects of M.Kopeev’s works - Сaлкынбaев М. Б. (Journal of Oriental Studies, 2018)
This article is devoted to kazakh and Arabic literature links of XX century on the works of M.Kopeyev and revealed among literary works Arabic motives. Subjectly-compositional structure of the parable in the works of M.Kopeyev compared with analogues in Arabic literature, Presented studies standing, developing the system of genre of the parable, ways of penetrationand its literary decisions base on national philosophy. And considered arabic sources in the works of M.Kopeyev and compared their literary distinction and similarity, revealing the specialty of the style of M.Kopeyev